Табірний зошит Ярослави Музики - Білокінь, С. (Студії мистецтвознавчі, 2011)
Публікація ознайомлює з недослідженим періодом життя видатної української художниці Ярослави Музики. Подається текст спогадів мисткині, що всебічно висвітлює її перебування в концтаборі. This publication reveals the part of life of an outstanding Ukrainian artist Yaroslava Muzyka, that has never been studied before. It presents excerpts from her memoires that provide a comprehensive picture of the time she had spent at a concentration camp.